Norm


D_i =||x_i-x_s||=\sqrt{(x_i-x_s)^2+(y_i-y_s)^2}

D_1^2-D_2^2=(x_1-x_s)^2+(y_2-y_s)^2-((x_2-x_s)^2+(y_2-y_s)^2)

D_1^2-D_2^2=x_1^2-2x_1x_s+x_s^2+y_1^2-2y_1y_s+y_s^2-x_2^2

+2x_2x_s-x_s^2-y_2^2+2y_2y_s-y_s^2

D_1^2-D_2^2=x_1^2+y_1^2-x_2^2-y_2^2+x_s^2-x_s^2+y_s^2-y_s^2

+2(x_2-x_1)x_s+2(y_2-y_1)x_s

D_1^2-D_2^2=||x_1||^2-||x_2||^2+2(x_2-x_1)x_s+2(y_2-y_1)y_s

Pos ini dipublikasikan di Tidak terkategori. Tandai permalink.

Tinggalkan Balasan

Isikan data di bawah atau klik salah satu ikon untuk log in:

Logo WordPress.com

You are commenting using your WordPress.com account. Logout / Ubah )

Gambar Twitter

You are commenting using your Twitter account. Logout / Ubah )

Foto Facebook

You are commenting using your Facebook account. Logout / Ubah )

Foto Google+

You are commenting using your Google+ account. Logout / Ubah )

Connecting to %s